A mouse model of Angelman syndrome imprinting defects. (26th September 2018) - Lewis, Michael W; Vargas-Franco, Dorianmarie; Morse, Deborah A; Resnick, James L
Abstract: Angelman syndrome, Prader–Will syndrome and Dup15q syndrome map to a cluster of imprinted genes located at 15q11-q13. Imprinting at this domain is regulated by an imprinting control region consisting of two distinct elements, the Angelman syndrome imprinting center (AS-IC) and the Prader–Willi syndrome imprinting center (PWS-IC). Individuals inheriting deletions of the AS-IC exhibit reduced expression of the maternally expressed UBE3A gene and biallelic expression of paternal-only genes. We have previously demonstrated that AS-IC activity partly consists of providing transcription across the PWS-IC in oocytes, and that these transcripts are necessary for maternal imprinting of Snrpn . Here we report a novel mouse mutation that truncates transcripts prior to transiting the PWS-IC and results in a domain-wide imprinting defect. These results confirm a transcription-based model for imprint setting at this domain. The imprinting defect can be preempted by removal of the transcriptional block in oocytes, but not by its removal in early embryos. Imprinting defect mice exhibit several traits often found in individuals with Angelman syndrome imprinting defects.